Pencegahan Rabies di Bali melalui Pendekatan Sosio-Kultural: Perspektif Berbasis Komunitas - Meli Rizki Purwani; Novendra Imanuel Sitepu (LPPM Institut Pendidikan Nusantara Global, 2026)
Rabies has remained a serious public health problem in Bali since the 2008 outbreak, despite widespread government interventions such as mass dog vaccination. However, program implementation faces obstacles such as low public awareness, the habit of letting dogs roam freely, and high birth rates. This study used a descriptive-qualitative approach through secondary data analysis from official reports, scientific publications, and health documents to examine the socio-cultural factors influencing rabies control in Bali. The findings indicate that top-down eradication programs have not fully accommodated the local cultural context, resulting in suboptimal program effectiveness. Involving traditional villages and respected community leaders has the potential to strengthen rabies prevention through Communication, Information, and Education (IEC) programs tailored to local socio-cultural characteristics. This strategy aligns with animal welfare principles through the promotion of responsible ownership, routine vaccination, and sterilization. Lessons learned from community-based rabies control practices in India and Thailand indicate that integrating local leadership can enhance program sustainability. The novelty of this study lies in its emphasis on socio-cultural integration into public health strategies, particularly in Bali, where traditional governance structures remain highly influential.